2017
DOI: 10.1186/s12913-017-2487-6
|View full text |Cite
|
Sign up to set email alerts
|

“I want to know everything”: a qualitative study of perspectives from patients with chronic diseases on sharing health information during hospitalization

Abstract: BackgroundPatient-centered care promotes the inclusion of the most prominent and important member of the health care team, the patient, as an active participant in information exchange and decision making. Patient self-management of a chronic disease requires the patient to bridge the gap between multiple care settings and providers. Hospitalizations often disrupt established self-management routines. Access to medical information during hospitalization reflects patients’ rights to partner in their own care an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 31 publications
(46 reference statements)
2
38
2
1
Order By: Relevance
“…The patients' own thoughts about their new situation can also influence how they cope. 6,7 Another aspect of coping with the new life situation is the type of support the patients can receive. The social support received depends on the patients' available network of people, and the need for social support will vary depending on the patients' age and need.…”
Section: Introductionmentioning
confidence: 99%
“…The patients' own thoughts about their new situation can also influence how they cope. 6,7 Another aspect of coping with the new life situation is the type of support the patients can receive. The social support received depends on the patients' available network of people, and the need for social support will vary depending on the patients' age and need.…”
Section: Introductionmentioning
confidence: 99%
“…Highlighting the role of the patient in particular could facilitate their participation [3,28,36]. To support collection, the record should support multiple kinds of data formats (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients in the hospital essentially “want to know everything” [3] about their health status and care in the hospital. However, existing information sources often do not meet their information needs [26,42].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations